Study process and proposal improvement of safety glass production / Mohd Fadzil Md Lazim - Md Lazim, Mohd Fadzil (2002)
Pre process : 1) Ensure conformity of raw glass from MSG warehouse2) Cutting, washing, drying Printing : 1) Ensure conformity of semi products from pre process2) Ensure conformity production material3) Printing of masking process Furnace : 1) Ensure conformity of semi product from printing: 2) Temper the semi products to customer requirement